Varying operating frequency of concentric circular ring patch antenna using high impedance surface - Orugu, Rangarao.; Gundapaneni, Srilatha.; Maryleena, N; K.Chaithanya Varma, A (International Journal of Engineering and Technology, 2018)
In this paper, we design a concentric circular patch antenna excited by microstrip feed and operates at 5.4269 GHz and 6.9419 GHz. After designing the antenna, we would like to tune the frequency without changing antenna size. For that purpose, we use high impedance surface structure to tune the antenna at two different frequencies. A simple mushroom like structure is used as high impedance surface. We will analyze antenna parameters like return loss, gain, directivity, radiation patterns, efficiency, proposed antenna with and without high impedance surfaces and compare the results.Â Â